Sains dan Agama dalam Epistemologi Islam dan Barat - Edwin Syarif (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
Science and religion are two important aspects that encompass human life. They complement each other within the individual, or conversely, they are at odds, demanding humans to choose between them. The latter stance characterizes the development of science in the modern era, where science becomes secular as it is solely based on the empirical and rational, while religion is not. In Islamic history, science and religion developed alongside each other. Islamic teachings often contain messages to observe the universe as a sign of the Creator's existence. Therefore, the development of science during the Islamic golden age was rapid. The issue of science and religion remains intriguing to study because modern science, which was initially hoped to solve human problems, has now become a problem for human life.